Effect of temperature on an elastic-plastic hemispherical asperity in contact with a rigid flat. (1st January 2011) - Loganathan, P.; Shankar, S.
The majority of surface effects are temperature dependent. The present work extends the Jackson and Green model (2005) for an elastic-plastic hemispherical asperity in contact with a rigid flat by including the temperature effects. The result initially shows that there is no change in end of elastic-plastic state or start of fully plastic regime when temperature increases at the contacting interfaces. But in practical applications, temperature effect plays an important role in determining the state transition. There is no change in the state transition from the present FEA results, because FEM packages utilize the elastic properties ( E ) and the yield strength ( Y ) as constant for the entire analysis. But the elastic modulus and yield will vary when the temperature is increasing. So, a methodology is presented and validated with the experimental observations in this paper to evaluate the variations in E / Y ratio with increasing temperature using the finite element concepts.